2018
DOI: 10.1192/bja.2018.26
|View full text |Cite
|
Sign up to set email alerts
|

Boundary violations in therapy: the patient's experience of harm

Abstract: SUMMARYHarm in talking therapies, and in healthcare professionals’ relationships with patients generally, has received little attention in comparison with harm by medication and other treatments. There has been little research into causes, types and effects. Professionals behave as if it does not happen and tend to react defensively to complaints. We believe that it is essential for professionals to understand the potential for harm and evaluate their actions in order to make them safer. This article defines h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 17 publications
(25 reference statements)
1
14
0
Order By: Relevance
“…In addition to the negative effects that sexual exploitation has on a person in any sphere of life, sexual boundary violations involving patients result in additional harm due to difficulties in trusting other professionals and accessing treatment. Sexual boundary violations are not always viewed (by the patient and others) as exploitation, because the effects of the power differential and factors such as adverse idealising transference (Hook 2018) are insufficiently recognised. Patients frequently feel a degree of complicity and lose trust in their own judgement.…”
Section: Harmful Effects Of Sexual Boundary Violationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the negative effects that sexual exploitation has on a person in any sphere of life, sexual boundary violations involving patients result in additional harm due to difficulties in trusting other professionals and accessing treatment. Sexual boundary violations are not always viewed (by the patient and others) as exploitation, because the effects of the power differential and factors such as adverse idealising transference (Hook 2018) are insufficiently recognised. Patients frequently feel a degree of complicity and lose trust in their own judgement.…”
Section: Harmful Effects Of Sexual Boundary Violationsmentioning
confidence: 99%
“…This is the second of two articles in BJPsych Advances considering harm arising from boundary violations in psychotherapy in particular and healthcare in general. The first (Hook 2018) discussed the general problem of harm in the therapeutic context and explored the adverse idealising transference. In this article we consider sexual boundary violation, its categories, the harm that ensues, the typologies of perpetrators, sanction and remediation, and finally suggestions for improving knowledge in the professions and safeguarding patients.…”
mentioning
confidence: 99%
“…In their second article Hook & Devereux (2018b) cite the study by MacDonald et al (2015) which found high levels of insecurity of attachment in doctors referred to a therapy programme for professional boundary violations. Insecure attachment might explain the adverse idealising transference described by Hook & Devereux (2018a), because idealisation is a key aspect of dismissing/avoidant attachment strategies. The dismissing stance deactivates distressing emotions and keeps them out of consciousness, and this results in both conscious dismissal of need (‘I'm fine, I don't need help’) and unconscious idealisation processes which keep painful or disturbing affects and thoughts out of consciousness.…”
Section: Dysfunctional Attachment Stylesmentioning
confidence: 99%
“…I am grateful to both the Editor of BJPsych Advances and to the authors of these two stimulating articles (Hook 2018a,b) for an opportunity to reflect on this most important of topics. Reading these articles reminded me of a conversation about sexual boundary violations by therapists that I had in 1990 with a senior and highly respected professor of psychiatry who was a leader in mental health ethics.…”
mentioning
confidence: 99%
“…In examining these issues, in this paper I will not include the impact of extreme events, catastrophic ruptures to the therapeutic frame and relationship (death, suicide or boundary violations) which a number of researchers have described (Crawford et al ., ; Deutsch, ; Hook & Devereux, , ; Sarkar, ) and which constitute experiences of betrayal or abandonment. Instead I shall be considering issues arising in normal psychotherapy practice, regardless of the therapist's theoretical orientation.…”
Section: Introductionmentioning
confidence: 99%